Is thirst sufficient as a mechanism for achieving euhydration? A narrative review - Capitán Jiménez, Catalina (2023)
The role of thirst perception for keeping hydric balance, both during and after exercise, has been extensively studied. However, the way to assess it and the effectiveness of the existing instruments are areas that still require further research. The objective of this review is to integrate, in a general way, the information available in the literature on the functioning of the thirst mechanism as a response to dehydration during and after exercise. The physiological mechanisms and their responses during and after exercise are explained. In addition, a description of the instruments available in scientific literature is included, together with their weaknesses and strengths, and a series of as yet unanswered questions in this area are raised. This review presents the theoretical aspect of thirst mechanisms, and discusses the scientific studies that support or refute the behavior of these mechanisms in exercise. Finally, a summary is made of the major conclusions drawn from the scientific literature on thirst as a sufficient mechanism to prevent dehydration both during and after exercise.